Integrasi Nilai Budaya Lokal pada Pembelajaran Pendidikan Agama Islam di Sekolah Dasar - Isti Hawa; Ahmad Suradi; Deko Rio Putra (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to examine the integration of local cultural values in Islamic Religious Education (IRE) learning at SD Negeri 03 Bengkulu Tengah. The research employed a qualitative descriptive approach to gain an in-depth understanding of the planning, implementation, and impact of integrating local culture into IRE learning. Data were collected through passive participant observation, semi-structured interviews, and documentation involving IRE teachers, students of grades IV, V, and VI, the school principal, and community figures. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings indicate that local cultural values such as mutual cooperation, deliberation, politeness, traditional ceremonies, and local customs have been contextually integrated into IRE learning. This integration contributes to improved student understanding, increased learning engagement, and the development of students’ religious character and social attitudes. The study concludes that integrating local cultural values is an effective learning strategy to create meaningful and contextually relevant Islamic religious education